Fantasional dalam Novel Haniyah dan Ala di Rumah Teteruga Karya Erni Aladjai - Firdhaus Budi Nyata (Journal on Education, 2022)
This study aims to understand the structure of the story in the novel Haniyah and Ala di Rumah Teteruga by Erni Aladjai with the narrative approach of Tzvetan Todorov's fantastical story. The purpose of fantastics is to interpret reality. Where the tension of something unreal collides with the existing reality. As a fantastic story, the novel "Haniyah and Ala di Rumah Teteruga" by Erni Aladjai is a manifestation of the author's fictional depiction of reality. Haniyah and Ala novels in the Teteruga House are not fictional stories that only provide entertainment. But there is also a message that the author wants to convey to readers and literary connoisseurs. To understand more deeply what appears to be explicit in the novel, fantastical stories are useful for intercession of the meaning of reality in the novel. Based on the results of the analysis, Haniyah and Ala novels in the Teteruga House belong to the class of pure fantastical stories. Because, at the beginning of the story, there is already a vacillation between the magical and the logical. Meanings that can be explained outside the structure of the novel include labeling and bullying that have a negative impact and attitudes that can be used as a reference to maintain tolerance, maintain tradition, and balance. Haniyah and Ala's novel at Teteruga's house also has a medium of storing reality that is not explicitly featured in the novel including the labeling and bullying experienced by the character impacting mental and physical health. Another meal that can be explained is related to efforts to maintain tolerance, especially between religious people and maintain traditions that have become a real means of environmental and ecological education to the next generation.